Copper oxide - perovskite mixed matrix membranes delivering very high oxygen fluxes - Leo, A.; Motuzas, J.; Yacou, C.; Liu, Shaomin; Serra, J.; Navarrete, L.; Drennan, J.; Julbe, A.; Diniz da Costa, J. (Elsevier BV, 2017)
Here we show that copper substitution in perovskite-type barium strontium cobalt copper oxide (BSCC) membranes confers extremely high oxygen fluxes well beyond the state of art, reaching 27.5 ml cm-2 min-1 at 950 °C. A key feature of BSCC is the formation of a mixed matrix catalyst-perovskite membrane caused by the segregation of copper, leading to the formation of an intergranular network of copper-rich oxide between perovskite grains. BSCC membranes delivered pressure normalised oxygen flux (i.e. permeance) of up to 86 times higher, above pressure difference of 18 kPa, as compared to best perovskite membrane, BBSC, due to the catalytic effect of segregated copper oxide. Unlike conventional dual-phase membranes which contain ion and electron conducting phases, this work shows for the first time perovskite-type membranes consisting of a mixed matrix of oxygen ion/electron conducting (perovskite) and catalytic (copper oxide) phases, thus paving the way to the development of high performance membranes for oxygen separation from air for clean energy applications.